Effects of dietary phosphorus and vitamin d3 supplementation on growth performance, antioxidant capacity, lipid metabolism, and phosphorus transport of hybrid yellow catfish (Pelteobagrus fulvidraco ♀ × Pelteobagrus vachelli ♂) - Jiali Jiang; Huimin Sun; Rui Wang; Meiqin Zhuo (Aquaculture Reports)
This study investigated the effects of dietary phosphorus levels and vitamin D3 (VD3) supplementation on the growth performance, antioxidant capacity, lipid metabolism, and phosphorus transport of hybrid yellow catfish (Pelteobagrus fulvidraco × Pelteobagrus vachelli). Six diets were formulated: five phosphorus levels (0.54 %, 0.65 %, 0.74 %, 0.98 %, 1.28 %) and one VD3 group (0.65 % phosphorus + 2000 IU/kg VD3). Each group had three replicates of 40 fish (4.00 ± 0.06 g initial weight). The trial lasted 56 days. The results demonstrated that dietary total phosphorus levels ranging from 0.65 % to 0.74 % promoted growth of hybrid yellow catfish, improved feed utilization and enhanced the hepatic antioxidant capacity. In contrast, low or high phosphorus levels inhibited growth, damaged liver health, and affected hepatic lipid deposition. Lipidomics of the 0.54 % and 0.74 % groups showed 0.74 % phosphorus reduced hepatic triglyceride (TG) and diacylglycerol (DG), while increased the levels of phosphatidylcholine (PC) and phosphatidylethanolamine (PE) through the glycerophospholipid pathway. qPCR results showed that increasing dietary phosphorus significantly upregulated the expression of slc20a1a and slc20a2, but had no significant impact on slc34a1a, slc34a2a, or slc34a2b in the liver of hybrid yellow catfish. Compared the 0.65 % group with the VD3 group, VD3 supplementation enhanced liver antioxidant capacity and transporter expression of phosphorus transporters, but reduced the growth of hybrid yellow catfish. Overall, this study defines optimal dietary phosphorus levels required for the growth and liver health of hybrid yellow catfish, which contributes to the sustainable development of the hybrid yellow catfish aquaculture industry.